ANALISIS PENGARUH KOMPONEN AKREDITASI TERHADAP PRESTASI KERJA LEMBAGA PAUD DI KOTA PALEMBANG - Damaiyanti, Heny; Mases, Yulius (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Based on RI Minister of Education Regulation No. 30 of 2005, Article 1 paragraph 1.: Non-Formal Education National Accreditation Agency, hereinafter referred to as BAN-PAUD, is an independent evaluation body that establishes the feasibility of programs and / or educational units in non-formal education pathways with reference to national education standards. Whereas in paragraph 2 contains: Accreditation of non-formal education is an activity of assessing the feasibility of a non-formal education unit based on criteria that have been established and carried out by BAN-PNF which results are realized in the form of recognition of program or unit eligibility ratings.Accreditation standards are in accordance with Government Regulation No. 19 of 2005, Article 2 paragraph 1, that: Standard Non-formal Education is a pathway to education outside formal education which can be carried out in a structured and tiered manner, in which the quality of education is guaranteed and controlled accordingly with the National Education Standards, for this reason, it is necessary to do an evaluation, accreditation and certification. The purpose of the study was to determine the effect of BAN - PAUD Accreditation on the work performance of PAUD institutions in Palembang City. How much influence 8 (eight) National Education Standards have been set by BAN-PAUD on PAUD Work Achievement in Palembang city, both individually and collectively.The research method uses quantitative analysis with validity test, reliability test, F test and t test. The results of the study show that the BAN-PAUD accreditation component is good on its own- alone and together show a significant influence on improving the work performance of the Early Childhood Education Institution (PAUD).